The Son of Homer – Ezra Pound’s Odyssey - Schade, Gerson (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2018)
Ezra Pound was obsessed with Ulysses. He identified with him throughout his Cantos, a work Pound opens by stealthily reworking a passage from an obscure 16th-century Latin translation of Homer’s Odyssey. The son of Homer Pound, Ezra led a Ulyssean life in various senses – leaving his home country only to return after his adventures, simulating madness, telling lies. He shares the lying and the way of life with his contemporary Lawrence of Arabia. Both translated the Odyssey and both, like Ulysses, lost all their friends (or alienated nearly everyone). All three were much despised for their habits, Ulysses in general by the Greek classical tragedians, Pound in particular by George Orwell, and Lawrence by practically everybody.